2021
DOI: 10.1111/jcmm.16596
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between SARS‐CoV‐2 and human long non‐coding RNAs

Abstract: The long non‐coding RNAs (lncRNAs) play a critical regulatory role in the host response to the viral infection. However, little is understood about the transcriptome architecture, especially lncRNAs pattern during the SARS‐CoV‐2 infection. In the present study, using publicly available RNA sequencing data of bronchoalveolar lavage fluid (BALF) and peripheral blood mononuclear cells (PBMC) samples from COVID‐19 patients and healthy individuals, three interesting findings highlighted: (a) More than half of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 16 publications
1
64
0
Order By: Relevance
“…Due to the apparent similarity between SARS-CoV-2 and SARS-CoV, it can be speculated that lncRNAs have differential transcription in response to SARS-CoV-2 infection. Meanwhile, a large number of abnormal expressions of lncRNAs were found in bronchoalveolar lavage fluid (BALF) and peripheral blood mononuclear cells (PBMC) from COVID-19 patients in recent studies, which further verified this idea (8).…”
Section: Viral Gene Expressionmentioning
confidence: 77%
See 3 more Smart Citations
“…Due to the apparent similarity between SARS-CoV-2 and SARS-CoV, it can be speculated that lncRNAs have differential transcription in response to SARS-CoV-2 infection. Meanwhile, a large number of abnormal expressions of lncRNAs were found in bronchoalveolar lavage fluid (BALF) and peripheral blood mononuclear cells (PBMC) from COVID-19 patients in recent studies, which further verified this idea (8).…”
Section: Viral Gene Expressionmentioning
confidence: 77%
“…In addition, the differential expression of lncRNA may reflect the physiological and pathological changes of human body. For instance, lncRNAs NEAT1 and MALAT1, were significantly upregulated in BALF samples from patients compared to healthy samples, which have been shown to be potential biomarkers for HIV infection (8,105). The further investigation revealed that both lncRNAs were negatively correlated with CAPN1, a cysteine protease involved in the influenza virus infection.…”
Section: Lncrna As a Diagnostic Biomarkermentioning
confidence: 90%
See 2 more Smart Citations
“… Alam and Lipovich, 2021 , Arora et al, 2020 , Calcagnile et al, 2021 , Chow and Salmena, 2020 , Cipolla et al, 2018 , COVID-19 Host Genetics Initiative, 2020 , Hardenberg and Luft, 2020 , Hoffmann et al, 2020 , Hosseini Rad Sm and McLellan, 2020 , Hubacek et al, 2021 , Laha et al, 2021 , Li et al, 2020a , Li et al, 2021 , Li et al, 2020b , Liu et al, 2020a , Liu et al, 2020b , Lorente et al, 2021 , Ma et al, 2015 , Matyášek and Kovařík, 2020 , Menon and Hua, 2020 , Moazzam‐Jazi et al, 2021 , Paniri et al, 2021 , Paniri and Akhavan-Niaki, 2020 , Saçar Demirci and Adan, 2020 , Torre‐Fuentes et al, 2021 , Volz et al, 2021 , Walensky et al, 2021 , Xue et al, 2019 , Zeberg and Pääbo, 2020 .…”
Section: Uncited Referencesmentioning
confidence: 99%